Outcome of Silicone Oil Removal in Eyes Undergoing 3-Port Parsplana Vitrectomy - Dr. Imran Ghayoor, Darakhshanda Khurram (Pakistan Journal of Ophthalmology, 2011)
Purpose: The present study was designed to evaluate the outcome of silicone oil removal in eyes, which underwent vitreoretinal surgery using silicone oil as internal tamponade. Material and Method: A total of 50 patients who under went 3-port parsplana vitrectomy with silicone oil used as an internal tamponade were enlisted in the month of March 2005 and April 2005 and were followed for the period of twelve months till March 2006. All the patients were selected by a convenience type of non-probability purposive sampling. Results: Out of 50 patients, at the end of study period 31 achieved anatomical success that is the completely flat retina, 16 of these eyes achieved functional outcome, which was defined as attainment of VA ? 5/200. 19 eyes suffered retinal redetachment, out of which in 8 eyes retinal redetachment occurred in 1st week and in rest subsequently. Conclusion: Retinal detachment after silicone oil removal is common. A fewer than half the detachments occur within the first week.